2020
DOI: 10.1038/s41380-020-0751-3
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal dysfunction and social interaction deficits in mice lacking the cystine/glutamate antiporter

Abstract: The astrocytic cystine/glutamate antiporter system xc− represents an important source of extracellular glutamate in the central nervous system, with potential impact on excitatory neurotransmission. Yet, its function and importance in brain physiology remain incompletely understood. Employing slice electrophysiology and mice with a genetic deletion of the specific subunit of system xc−, xCT (xCT−/− mice), we uncovered decreased neurotransmission at corticostriatal synapses. This effect was partly mitigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 70 publications
2
28
2
Order By: Relevance
“…This transport system is necessary for redox balance and regulation of extracellular glutamate concentrations [188] by cooperating with excitatory glutamate transporters [189]. The deletion of xCT in mice produced less presynaptic mitochondria in the dorsolateral striatum and behavioral deficits associated with ASD [190]. This study highlights the significant role of astrocytes in ASD.…”
Section: Genetic Mutations Related To An Asd-like Clinical Syndromementioning
confidence: 74%
See 1 more Smart Citation
“…This transport system is necessary for redox balance and regulation of extracellular glutamate concentrations [188] by cooperating with excitatory glutamate transporters [189]. The deletion of xCT in mice produced less presynaptic mitochondria in the dorsolateral striatum and behavioral deficits associated with ASD [190]. This study highlights the significant role of astrocytes in ASD.…”
Section: Genetic Mutations Related To An Asd-like Clinical Syndromementioning
confidence: 74%
“…Understanding how synaptic mitochondria contribute to different neuronal populations in disease states could help to elucidate and develop novel therapeutic options to treat ASD and ASD-related neurodevelopmental disorders more effectively. [190] Reduced presynaptic mitochondrial population…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics has long played an indispensable role in the discovery and verification of biomarkers for brain disorders [ 17 ], and studies are increasingly oriented towards exploring the pathological mechanisms underlying various brain disorders. In a recently published work, researchers found that the astrocytic cystine/glutamate antiporter system xc(-) regulated corticostriatal neurotransmission, and influenced social preference and repetitive behavior in mice, providing important clues toward the neural mechanisms related to ASD and obsessive–compulsive disorder [ 226 ]. Synaptic proteome abnormalities related to several psychiatric disorders have been revealed in the last decade, and a number of signaling pathways are involved [ 54 , 160 , 227 , 228 ].…”
Section: Trends In Neuroproteomicsmentioning
confidence: 99%
“…This method has been applied to multiple datasets and predictions have been experimentally validated in our laboratory through individual kinase activity assays and inhibitor studies (Bentea et al, 2019;Bentea et al, 2020;Dorsett et al, 2017;Flaherty et al, 2019;McGuire et al, 2017;Schrode et al, 2019). An early version of KRSA, containing only the random sampling algorithm, identified altered phosphorylation of peptides and subsequently perturbed kinase activity in the anterior cingulate cortex (ACC) between schizophrenia and control subjects (McGuire et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…KRSA also was used to analyze kinome signatures of genetic perturbation of NRXN1 and FURIN1 in human induced pluripotent stem cell (hiPSC)-derived neurons (Flaherty et al, 2019;. More recently, KRSA has been utilized to analyze the kinome signature of mice with a genetic deletion of a specific subunit of cystine/glutamate antiporter system (xCT −/− mice) (Bentea et al, 2020). All of these published studies required significant use of multiple tools, some closed-access, and statistical expertise for quality control, network growth, pathway enrichment, and manually created graphs, heatmaps, and networks for visualization purposes.…”
Section: Introductionmentioning
confidence: 99%